(untitled) (Revista de Ciências Agroveterinárias, 2023)
The use of cover crops, especially in summer in off-season, is an uncommon practice because they compete with crops of economic importance. The objective was to evaluate the use of cover crops, soil cover and suppression of weeds in the corn-wheat off-season in northwest of Rio Grande do Sul. For this, sunn hemp, gray mucuna, jack bean, lupine, buckwheat, millet, millet, and sunn hemp intercrop (50%) and fallow (control) were used. The species were sown after harvesting the corn crop with 0.45 m spacing between rows in randomized blocks with six replications. The soil cover rate was analyzed at 30, 45, 60, 75 and 90 days after sowing. Dry matter was determined at full flowering of each crop, separated into stalks/stems and leaves, and dried at 65ºC. The incidence of weeds was evaluated at the time of full flowering. In the off-season, millet, millet + crotalaria, gray mucuna and jack bean intercropped have greater soil cover efficiency, both reaching 100% soil cover. The highest accumulations of dry matter were from millet (11,204 kg.ha-1) and intercropped (9291 kg.ha-1). The most efficient crops for the suppression of weeds were pearl millet, intercropped and gray mucuna. Sunn hemp and buckwheat showed low performance; therefore, they are not recommended for single cultivation in the corn-wheat off-season.